2020
DOI: 10.3390/molecules25051018
|View full text |Cite
|
Sign up to set email alerts
|

A New Positron Emission Tomography Probe for Orexin Receptors Neuroimaging

Abstract: The orexin receptor (OX) is critically involved in motivation and sleep−wake regulation and holds promising therapeutic potential in various mood disorders. To further investigate the role of orexin receptors (OXRs) in the living human brain and to evaluate the treatment potential of orexin-targeting therapeutics, we herein report a novel PET probe ([11C]CW24) for OXRs in the brain. CW24 has moderate binding affinity for OXRs (IC50 = 0.253 μM and 1.406 μM for OX1R and OX2R, respectively) and shows good selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…As shown in Table , the lipophilicity increased as the alkyl chain extended. Log D 7.4 values of 3a and 6a were tested based on a shake-flask method . The results showed that 6a possesses lipophilicity with Log D 7.4 < 3.5, indicating a high likelihood of achieving sufficient brain permeability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table , the lipophilicity increased as the alkyl chain extended. Log D 7.4 values of 3a and 6a were tested based on a shake-flask method . The results showed that 6a possesses lipophilicity with Log D 7.4 < 3.5, indicating a high likelihood of achieving sufficient brain permeability.…”
Section: Resultsmentioning
confidence: 99%
“…The general procedure for log D determination assays as described in our previous literature. , Briefly, 10 μL of 3a or 6a in DMSO solution (10 mM) was mixed with 100 μL of octanol in PBS buffer (pH 7.4) and followed by shaking in a rotator for 1 h at 30 rpm. Incubations are done in duplicates.…”
Section: Methodsmentioning
confidence: 99%
“…The general procedure for rodent PET/CT studies was described previously ( Bai et al, 2019 , 2020a ). Briefly, the PET/CT scan was carried out by a Triumph Trimodality/SPECT scanner (Gamma Medica, Northridge, CA, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Positron emission tomography (PET) imaging is a unique tool that can give the answers to these essential questions about BET BD1 and BD2 in living subjects in a noninvasive way. 25 With a suitable radiotracer, PET imaging would accelerate BET research to aid investigators in diagnosing disease, monitoring treatment, and in drug development. However, developing the PET radioligand targeting BET BD1 and BD2 with high binding affinity and high selectivity is demanding and challenging.…”
mentioning
confidence: 99%
“…Provirus studies have found that BRDs (BRD2/3/4) are highly distributed in various tissues and organs, especially in the liver, kidney, and lung, which is consistent with our findings. 25,28,29 As an important application of PET imaging, it could be used for disease diagnosis such as brain disorders and tumors. Because [ 18 F]PB006 has specific binding in peripheral organs such as the lungs and heart, there is potential to apply this probe for tumor imaging such as NUT midline carcinoma.…”
mentioning
confidence: 99%